Strategi Guru SD dalam Menanamkan Sikap Toleransi melalui Pembelajaran PPKn - Zaskia Nazwa; Anwar Sidik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Indonesia’s multicultural diversity poses serious challenges in maintaining social harmony, marked by increasing cases of intolerance driven by differences in ethnicity, religion, and culture. Education, particularly civics (PPKn), plays a strategic role in instilling tolerance values from an early age. This study aims to analyze the strategies used by elementary school teachers in cultivating tolerance attitudes through PPKn learning, identify the implementation of tolerance values in classroom activities and student social interactions, and reveal the challenges faced by teachers along with effective and contextual learning strategies. This study employed a qualitative descriptive approach based on library research, collecting data from accredited scientific journals published between 2021 and 2025, sourced from databases including google scholar, DOAJ, and sinta- indexed journals. Data were analyzed using descriptive qualitative analysis through stages of data reduction, data presentation, and conclusion drawing, with source triangulation appliet to ensure validity. The findings reveal that affective teachers employ a holistic approach encompassing cognitive, affective, and psychomotor domains, consistent with Bloom’s revised taxonomy. Teachers serve not only as knowledge transmitters but also as moral role models, as supported by Bandura’s Social Learning Theory. Implementation is carried out through three channels: intracurricular, co-curricular, and extracurricular activities. Key challenges include dominance of cognitive approaches, limited understanding of multicultural education, and negative influencesof social media. This study implies the urgent need for continuous professional training for PPKn teachers, differentiated and inclusive learning design, and active collaboration between schools and families to strengthen the internalization of tolerance values in elementary school students.